2022
DOI: 10.3390/antibiotics11040465
|View full text |Cite
|
Sign up to set email alerts
|

Terazosin Interferes with Quorum Sensing and Type Three Secretion System and Diminishes the Bacterial Espionage to Mitigate the Salmonella Typhimurium Pathogenesis

Abstract: Salmonella enterica is an invasive intracellular pathogen and hires diverse systems to manipulate its survival in the host cells. Salmonella could eavesdrop on the host cells, sensing and responding to the produced adrenergic hormones and other neurotransmitters, which results in the augmentation of its virulence and establishes its accommodation in host cells. The current study aims to assess the anti-virulence effect of α-adrenergic antagonist terazosin on S. Typhimurium. Our findings show that terazosin sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 64 publications
0
38
0
Order By: Relevance
“…Use of inhibiting substances that interfere with the quorum sensing (QS) is one of the preventative measure for enhancing food quality and safety [ 31 , 32 ]. One of them targets QS, a mechanism that allows cells to communicate with one another and allows germs to survive under adverse conditions [ 33 , 34 ]. When bacterial concentrations approach a predetermined concentration threshold, signaling molecules or auto-inducers are secreted, which control the expression of virulence genes at bacterial densities [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of inhibiting substances that interfere with the quorum sensing (QS) is one of the preventative measure for enhancing food quality and safety [ 31 , 32 ]. One of them targets QS, a mechanism that allows cells to communicate with one another and allows germs to survive under adverse conditions [ 33 , 34 ]. When bacterial concentrations approach a predetermined concentration threshold, signaling molecules or auto-inducers are secreted, which control the expression of virulence genes at bacterial densities [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…When bacterial concentrations approach a predetermined concentration threshold, signaling molecules or auto-inducers are secreted, which control the expression of virulence genes at bacterial densities [ 34 ]. Numerous virulence factors, such as the production of nuclease, hemolysin, lipase, protease, and prodigiosin, as well as the development of biofilms and motility, are regulated by QS [ 33 , 34 ]. QS in many bacteria can be disrupted by phenolic chemicals generated from plants [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Virulence factors play a key role in the establishment of bacterial infection, guarantee bacterial spreading, escape from the immune system, and even enhance the resistance to antibiotics [ 6 , 8 ]. Bacterial virulence is controlled by interplayed systems to regulate bacterial invasion and accommodation in the host tissues [ 3 , 9 ]. Quorum sensing (QS) plays a crucial role in regulating virulence factor production.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that terazosin and prazosin had the most significant ability to interfere with several QS receptors [ 26 ]. Furthermore, terazosin showed significant anti-virulence activities and diminished the virulence of Pseudomonas aeruginosa [ 26 ] and Salmonella Typhimurium [ 9 ]. These findings encouraged us to assess the anti-QS and anti-virulence activities of prazosin on Gram-negative bacteria while Chromobacterium violaceum as well as, Pseudomonas aeruginosa , Proteus mirabilis , and Serratia marcescens were chosen due to their famed involvement in aggressive infections and significant multidrug resistance profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations showed that farmed rabbits are predisposed to L. monocytogenes, and their meat is a potential source of listerial foodborne pathogens [ 11 , 12 ]. The hardiness of L. monocytogenes against eradication is due to its capacity to adapt and persist in a variety of environments, its intracellular site, and the weak intracellular diffusion of some antibiotics, which makes it a serious ongoing concern in animal production [ 13 , 14 ]. Additionally, the virulence of L. monocytogenes arises from its ability for invasion, adhesion, and translocation across the intestinal barrier throughout the gastrointestinal phase of infection [ 15 ].…”
Section: Introductionmentioning
confidence: 99%